2014
DOI: 10.1371/journal.pone.0100629
|View full text |Cite
|
Sign up to set email alerts
|

Nfatc2 and Tob1 Have Non-Overlapping Function in T Cell Negative Regulation and Tumorigenesis

Abstract: Nfatc2 and Tob1 are intrinsic negative regulators of T cell activation. Nfatc2-deficient and Tob1-deficient T cells show reduced thresholds of activation; however, whether these factors have independent or overlapping roles in negative regulation of T cell responses has not been previously examined. Here, we show that Nfatc2 knockout (KO) but not Tob1 KO mice have age-associated accumulation of persistently activated T cells in vivo and expansion of the CD44+ memory cell compartment and age-associated lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“… 4 Recently, it was shown that NFAT1 −/− mice also develop spontaneous B-cell lymphomas. 123 Taken together, these results support an opposite role for NFAT1 and NFAT2 in the regulation of tumorigenesis.…”
Section: Nfat and Tumorigenesismentioning
confidence: 68%
“… 4 Recently, it was shown that NFAT1 −/− mice also develop spontaneous B-cell lymphomas. 123 Taken together, these results support an opposite role for NFAT1 and NFAT2 in the regulation of tumorigenesis.…”
Section: Nfat and Tumorigenesismentioning
confidence: 68%
“…Sikander et al [51] demonstrated that there may be a potential association between polymorphisms in the (SERT) gene promoter and UC, thus STX3 seems to be important for UC pathogenesis. Considering NFATC2, we know that it is a transcription factor with pleotropic roles [52]. Remarkably, the existing data suggest an important cell-intrinsic role for NFAT family transcription factors in intrinsic negative T cell regulation and Weigmann et al [53] supported that oxazolone-induced ulcerative colitis and progression to colon cancer are attenuated in NFATC2 KO mice due to ineffective production of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…NFAT1-deficient mice older than 16 months spontaneously develop B cell neoplasms with features of anaplastic and/or plasmablastic plasmacytomas. 58 However, the molecular mechanisms for preferential formation of B cell malignancies in age-associated NFAT1-deficient mice were not elucidated. Regarding the role of NFAT1 in other systems, it has been shown that lack of NFAT1 induces neoplastic transformation of cartilage cells and increased susceptibility to chemically-induced sarcoma formation in mouse models.…”
Section: Discussionmentioning
confidence: 99%